Teknologi Desain Alat Pencelupan Pewarnaan di UKM Batik Dewandaru di Kecamatan Wonosari Kabupaten Malang - Qurrata, Vika Annisa; Yusida, Ermita; Sudjatmiko, Sudjatmiko; Fajar, Lustina (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
Batik Tulis Dewandaru UKM only does batik coloring. The method is done by dipping the batik into a tub and then shaking it by the operator, causing an awkward and less functional posture. Based on the above problems, the Community Service team provided a solution to implement dyeing and fixation technology. The first part is an oil drum made from Galvanized Steel Sheets JIS G3302 SGCC with a thickness of 1.8 mm, a sufficient 20 liters volume. It is equipped with a stainless steel pipe roller SS 304. The second part is a frame made of angled iron (L40x40x3), 50x50x1,25 hallow iron. , frame dimensions 1940 mm (W) x 660 mm (W) x 1600 mm (H). The third part of the fabric support pipe with a total of 4 (cross), is made of SS 304 stainless steel pipe material, 1870 mm long. The fourth part of the player, made of SS 304 stainless steel pipe material, 325 mm long, doubles as a media to rotate the cloth and drain it. The tool, which weighs 75 kg, makes the dyeing process shorter, which is 11 minutes. With the new tools, crafters can dye up to 35 fabrics to produce more fabric with perfect coloring.DOI:Â https://doi.org/10.26905/abdimas.v5i3.4977Â